(untitled) (Research, Society and Development, 2023)
This research aimed to investigate elements of teaching practice that trigger motives for studying and their implications in the processes of appropriation of scientific knowledge and human development. This is a Case Study developed in a state public school located in the Northwest of the State of Rio Grande do Sul, which involved 90 students, who answered a printed questionnaire during the class period, which addressed aspects related to the teaching activities and study and the elements that produce reasons for this research. Ten teachers who worked in high school were also involved, participating in an interview held at the school. Through Discursive Textual Analysis (DTA) two categories emerged: a) work and b) omnilateral training. The results reveal that the study activity determines the emergence of the main psychological neoformations of school age, and show that students need to be taught to organize their cognitive activity and that the production of reasons for studying must be related to the student’s need appropriating historical-social knowledge, becoming heirs of culture, becoming humanized.